2010
DOI: 10.1007/s12017-010-8128-4
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic autoimmune demyelinating disease of the CNS. Oligodendrocytes, the myelin forming cells of the central nervous system (CNS), are target cells in MS. Although the etiology of MS is poorly known, new insights suggest oligodendrocyte apoptosis as one of the critical events followed by glial activation and infiltration of lymphocytes and macrophages. A major breakthrough in delineation of the mechanism of cell death, perivascular cuffing and glial activation came from elucidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 101 publications
(110 reference statements)
1
55
0
Order By: Relevance
“…The bands at 2853 and 2885 cm −1 are derived from lipids, 21,22 and peripheral nerve tissue is rich in lipids in myelin sheaths that surround axons to support neural electrical activity. [28][29][30][31] Myelin is supplied by Schwann cells and myelin lipids include sphingomyelin and the glycolipid galactocerebroside. Schwann cells had similar spectral patterns at 2851 and 2885 cm −1 and Raman spectra of sphingomyelin showed similar patterns to that of Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…The bands at 2853 and 2885 cm −1 are derived from lipids, 21,22 and peripheral nerve tissue is rich in lipids in myelin sheaths that surround axons to support neural electrical activity. [28][29][30][31] Myelin is supplied by Schwann cells and myelin lipids include sphingomyelin and the glycolipid galactocerebroside. Schwann cells had similar spectral patterns at 2851 and 2885 cm −1 and Raman spectra of sphingomyelin showed similar patterns to that of Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of MS is unclear, new insights suggest oligodendrocyte apoptosis as one of the critical events in physiological and pathophysiological processes [41]. Several studies have revealed that cytokine and ionic imbalance are the most important factors in axonal degeneration through inducing neuron mitochondrial dysfunction, alteration of ion exchange mechanisms and energy failure [42].…”
Section: Asics and Multiple Sclerosismentioning
confidence: 99%
“…The role of the T-cell sphingolipid metabolism on the Th17 differentiation or function has not been explored. Interestingly though, altered sphingolipid metabolism is associated with pathogenesis of multiple sclerosis, 44 and externally added sphingolipids augment Th17 differentiation. 45 We also validated the Th17 cell-associated up-regulation of long noncoding RNA MIAT, mRNA of structural protein COL6A3 encoding ␣-3 chain of the type VI collagen, and LMNA which is one of the nuclear lamina proteins.…”
Section: Org Frommentioning
confidence: 99%